Testimonies of the Nuremberg merchant Hans Tetzel (1518-1571) in Cuba: A historical and socio-linguistic analysis (Islas, 2023)
Introduction: The aim of this paper is to show the historical circumstances of this undertaking with a focus on the relations between Nuremberg and Cuba, the training of Hans Tetzel and the possibilities of studying a foreign language (Spanish) at this time. In addition, some of the German and Spanish documents in the archives are presented.Methods: The analysis of manuscript documents and the historical method are used as fundamental methodological elements.Results: Hans Tetzel from Nuremberg was the first to extract, smelt and purify copper in Cuba. He came to Seville and later to Santiago de Cuba thanks to the international network of Nuremberg, the great trade center for different minerals and their high-quality products. He acquired knowledge in foreign languages, thus it was possible for him as a foreigner in Spain to receive the right to exploit copper mines in the New World.Conclusions: According to the analysis of the manuscripts, Hans Tetzel's success was based on his knowledge about the production of high-quality copper, probably acquired in the mining industries of his relatives and acquaintances in Nuremberg. Hans Tetzel constituted the base of the exploitation of copper in Cuba for the following centuries.
Keywords: Hans Tetzel; archival documents; copper mining; Cuba; Nuremberg